2016
DOI: 10.11149/jkaoh.2016.40.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the whitening and remineralization effects of a mixture of amorphous calcium phosphate, hydroxyapatite and tetrasodium pyrophosphate on bovine enamel

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0/), which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. Objectives:The purpose of the present study was to evaluate the whitening effect, morphological and structural changes, and remineralization of the enamel induced by 3 combined agents: amorphous calcium phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Therefore, there is the need of innovative whitening agents to overcome the limitations of current materials. CaPs can fill this role, and several research works have already proved this [107][108][109][110][111][112][113][114][115][116][117][118]. CaPs as whitening agents have been proposed as innovative abrasive agents, as carrier of peroxides, or as adjuvant of bleaching agents.…”
Section: Oral Carementioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, there is the need of innovative whitening agents to overcome the limitations of current materials. CaPs can fill this role, and several research works have already proved this [107][108][109][110][111][112][113][114][115][116][117][118]. CaPs as whitening agents have been proposed as innovative abrasive agents, as carrier of peroxides, or as adjuvant of bleaching agents.…”
Section: Oral Carementioning
confidence: 99%
“…In this regard, the distinction of CaPs between cosmetic ingredients and therapeutic ingredients is labile because CaPs have a two-fold whitening action: (i) as an abrasive, to remove the stains by mechanical friction, and (ii) as a remineralizing ingredient, to restore the enamel structure and improve light scattering and absorption, leading to teeth brightness and whiteness [109,112,116]. In addition, it was demonstrated that the remineralization action of CaPs makes the enamel surface smoother and less prone to staining [113,116]. The whitening effect of CaPs has been studied in vitro [116], ex vivo [109][110][111][112][113][114][115], and in vivo [107,108,115,116].…”
Section: Oral Carementioning
confidence: 99%
See 3 more Smart Citations